Dual-cavity dual-output multi-wavelength fiber laser based on nonlinear polarization rotation effect - Tan, S.J.; Harun, Sulaiman Wadi; Shahabuddin, N.S.; Arof, Hamzah; Ahmad, Harith (IOP Publishing, 2012)
We demonstrate a multi!wavelength fiber laser based on nonlinear polarization rotation (NPR) in dual-cavity configuration with two output ports. The laser employs a piece of erbium doped fiber (EDF) and semiconductor optical amplifier (SOA) as the gain medium in a separate cavity. By incorporating PCF in the dual cavity the non-linear polarization rotation (NPR) effect is enhanced and thus higher output and more oscillating lasing can be achieved. The laser produces three strong lines with a spacing of 2.40 nm and side mode suppression ratio (SMSR) of more than 10 dB at 1535 nm region. Another output produces 8 lines of optical comb with a spacing of 0.54 at 1570 nm region.